The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0078120
|View full text |Cite
|
Sign up to set email alerts
|

Effective Population Size, Genetic Variation, and Their Relevance for Conservation: The Bighorn Sheep in Tiburon Island and Comparisons with Managed Artiodactyls

Abstract: The amount of genetic diversity in a finite biological population mostly depends on the interactions among evolutionary forces and the effective population size (N e) as well as the time since population establishment. Because the N e estimation helps to explore population demographic history, and allows one to predict the behavior of genetic diversity through time, N e is a key parameter for the genetic management of small and isolated populations. Here, we explored an N e-based approach using a bighorn sheep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 76 publications
1
10
0
Order By: Relevance
“…Genetic compensation could maintain genetic variation in PBS if certain social behaviors are density dependent. Gasca-Pineda et al (2013) found similar levels of genetic diversity in a bighorn sheep population established from only 16 individuals. These authors suggested that decreased predation pressure may have resulted in less sexual segregation, allowing females to mate with non-dominant males within the herd.…”
Section: Population Bottlenecks and Genetic Diversitymentioning
confidence: 58%
“…Genetic compensation could maintain genetic variation in PBS if certain social behaviors are density dependent. Gasca-Pineda et al (2013) found similar levels of genetic diversity in a bighorn sheep population established from only 16 individuals. These authors suggested that decreased predation pressure may have resulted in less sexual segregation, allowing females to mate with non-dominant males within the herd.…”
Section: Population Bottlenecks and Genetic Diversitymentioning
confidence: 58%
“…Similarly, depressed genetic diversity can also be seen in island bighorn sheep populations when compared to that of mainland populations (Gasca‐Pineda et al . ). Contemporary observations in other alpine species also tend to find that small isolated populations possess less genetic diversity (Henry et al .…”
Section: Discussionmentioning
confidence: 97%
“…Although effective population size and genetic diversity are typically associated, previous studies have shown that these two diversity estimates can become uncoupled due to differential gene flow and/or demographic processes (e.g., bottlenecking) acting through time (Gasca-Pineda, Cassaigne, Alonso, & Eguiarte, 2013;Lonsinger, Adams, & Waits, 2018;Miller & Waits, 2003). Given that our study deals with gene flow between wild and domestic lineages, we posit that gene flow from an inbred domestic lineage (e.g., game-farm mallards) can move "novel" variation into a population and thus create a signature of increased or similar effective population size as es- Similarly, we hypothesize that differential gene flow of loci across the genome from game-farm mallards into wild mallards may also explain the increased genomic differentiation observed across time between wild mallards and black ducks (Figure 3; Supplementary Materials Figure S2B Figure 4).…”
Section: Impact Of Differential Gene Flow On Genomic Diversity and mentioning
confidence: 99%